Introduction to Gender in Early Childhood Assisted by Flash Card Media - Wahyuni, Dwi; Jubaidah, Asih; Anitasari, Dhesy; Jarwanti, Jarwanti; Giyatmi, Giyatmi; Rahayu, Martini; Sulistyaningsih, Sulistyaningsih; Katoningsih, Sri (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2024)
One of the knowledge that children must know and have is about gender. Gender is the difference in characteristics possessed by a man or a woman. One media that can be used to introduce gender to children is flash card media. The aim of this research is to determine the effectiveness and advantages of flash cards in introducing gender to young children. This research uses a descriptive method with a qualitative approach. The research was conducted at Aisyiyah 03 Jatipuro Kindergarten, with subjects of 10 group A children aged 4-5 years. The results of the research show that through the use of flash card media for introducing gender to young children, children can better understand each gender characteristic of men and women. Flash cards were chosen because they are easy to make and cost effective, practical in use and storage, can be used anywhere, both at home and at school, and have an attractive appearance so that children are more enthusiastic about learning. The conclusion of the research is that flash card media can be used as an effective medium to introduce gender to young children based on the biological function of sex, how to dress and physical characteristics according to each gender.